Binge-Watching and Interpersonal Communication Patterns among Solo Raya Students: A Thematic Analysis - Raihan Abiyu Darda; Laili Etika Rahmawati (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The phenomenon of binge-watching has become part of the rapidly growing digital media culture, especially among college students. The activity is not only for entertainment but also to relieve stress and avoid academic pressure. This study explores how college students in Solo Raya interpret their binge-watching experiences and how these experiences impact interpersonal communication patterns. Using a descriptive qualitative approach, involving three university students selected through purposive sampling. Data were collected through semi-structured in-depth interviews and analyzed using thematic analysis. The study's results reveal five main themes. First, binge-watching is interpreted as a form of emotional coping with academic stress. Second, the main motivation for students to watch is facilitated by digital platform features such as on-demand and autoplay. Third, students experience ambivalence between the enjoyment of watching and the disadvantages experienced, such as physical fatigue and distracted focus. Fourth, digital content consumption serves as a means to create closer friendships through shared interests. Fifth, binge-watching contributes to increased knowledge and identity formation. With only three participants, the findings reflect individual experiences rather than broader generalizations. Binge-watching is a means of sharing experiences and a social resource in students' lives through digital content.